The Seleucid and Hasmonean periods and the apocalyptic worldview: The First Enoch Seminar Nangeroni Meeting Villa Cagnola, Gazzada (June 25-28, 2012) - Grabbe, Lester L.; Boccaccini, Gabriele; Zurawski, Jason (The Library of Second Temple Studies, 2016)
"This tightly focused collection of essays, from an invited seminar of international specialists, centres on the question of the apocalyptic worldview around the time of the Maccabean revolt. What was the nature of apocalyptic at this time? Did the Maccabees themselves have a distinct apocalyptic worldview? These questions lead to other, more specific queries: who of the various groups held such a view? Certain of the essays analyse the characteristics of the apocalypses and related literature in this period, and whether the apocalyptic worldview itself gave rise to historical events or, at least, influenced them. The collection begins with two introductory essays. Both the main and short papers have individual responses, and two considered responses by well-known experts address the entire collection. The volume finishes with a concluding chapter by the lead editor that gives a perspective on the main themes and conclusions arising from the papers and discussion."--Bloomsbury Publishing